Identification of a Papain-Like Protease Inhibitor with Potential for Repurposing in Combination with an Mpro Protease Inhibitor for Treatment of SARS-CoV-2 - Campagna, Jesus; Jagodzinska, Barbara; Alvarez, Pablo; Yuen, Constance; Enquist, Kathryn M; Cohn, Whitaker; Fajtová, Pavla; O’Donoghue, Anthony J; Arumugaswami, Vaithilingaraja; Li, Melody MH; Damoiseaux, Robert; John, Varghese (Archives of Clinical and Biomedical Research, 2022)
SARS-CoV-2 requires two cysteine proteases for viral polypeptide processing to allow maturation and replication: the 3C-like protease also known as the Main protease (Mpro) and the papain-like protease (PLpro). In addition to its critical role in viral replication, PLpro removes post-translational modifications like ubiquitin and interferon-stimulated gene product 15 (ISG15) from host proteins through its deubiquitinase domain, leading to host immunosuppression and increased ability of the virus to evade the host antiviral immune response. Through screening of a custom clinical compound library, we identified eltrombopag (DDL-701), a thrombopoietin receptor agonist, as having PLpro inhibitory activity that is sustained in the presence of the Mpro inhibitor nirmatrelvir. DDL-701 also suppressed both the deubiquitinase and ISG15 cleavage activities of PLpro. In addition, DDL- 701 partially restored interferon-β induction – an element of the host immune response – in an in vitro model system. Further, modeling and docking studies suggest DDL-701 interacts with the active site region of the PLpro enzyme and pilot pharmacokinetic studies indicate it is brain permeable. DDL-701 is already FDA approved for treatment of thrombocytopenia and has previously been shown to achieve human plasma levels after oral dosing that is above the IC50 needed for it to exert its PLpro inhibitory activity in vivo. In addition, it has also been reported to have antiviral efficacy against SARS-CoV-2. DDL-701 thus represents an excellent drug candidate that can immediately be repurposed and undergo clinical evaluation as a PLpro inhibitor, that most effectively in the clinic may be used in a protease inhibitor cocktail with an Mpro inhibitor such as nirmatrelvir (Paxlovid) for the treatment of COVID-19.